'Grand challenge' or 'not an issue'? The discourses on income inequality of compensation managers and consultants. Issue 20 (9th November 2021) - Guerci, Marco; Canterino, Filomena; Carollo, Luca; Dorigatti, Lisa; Mori, Anna
Abstract: Within the broader debate on the increase of labor income inequality, social concerns have growingly focused on organizational practices. Among these, market-oriented compensation practices, with their extensive pay dispersion, are deemed crucial 'inequality-generators'. Based on 49 interviews with Italian compensation managers and consultants, this article explores whether, in their talk, these actors align with (or detach from) inequality-increasing compensation practices, and which discourses they employ to justify their posture. By resorting to the discourses on meritocracy and market, the respondents fully supported dispersed market-based compensation structures, thus endorsing a motivation- (rather than legitimacy-) centered approach informed by a shareholder (rather than a stakeholder) perspective. In countering possible criticisms, they advanced two main discursive responses: 'transparent communication', i.e. communication intended to convince critics about the benefits of merit-based and market-based pay dispersion; and 'populism', i.e. a term used to discredit those critics that question any type of pay dispersion. Assuming a discursive approach, the paper adds an HRM perspective to the growing debate on the role of organizations in producing and re-producing income inequality, while critically showing that compensation managers and consultants fail as a resource for inequality reduction.